Structural modification of defective WO3 by g-C3N4 for photocatalytic gold recovery from non-cyanide-based plating effluent - Pimchanok Longchin; Tesfaye Tadesse Gebremariam; Naphaphan Kunthakudee; Auttawit Thoumrungroj; Thanapol Sutthiphong; Mali Hunsom (Scientific Reports)
Abstract A set of nCN/WO3 − x composites was synthesized through a simple thermal treatment for gold recovery from the simulated effluent of a non-cyanide-based plating bath. The obtained results exhibited that all nCN/WO3 − x composites demonstrated a higher photocatalytic activity for gold recovery than their pristine components due to the formation of nanocomposites which paved a convenient pathway for charge transfer. Among all synthesized composites, the 5.0CN/WO3 − x composite exhibited the highest photocatalytic activity, recovering around 69.4% of gold within 120 min under UV-vis light irradiation at an intensity of 3.45 mW/cm² and a catalyst loading of 1.0 g/L, in the absence of hole scavenger. This result can be ascribed to the presence of an optimal number of defects, which can act as electron trapping sites and thereby reduce the recombination rate of charge carriers. Gold recovery increased with repeated reuse, attributed to the decorated gold, which enhances light absorption and decreases the recombination rate of charge carriers. The feasible application of used CN/WO3 − x were also explored for H2 production, dye degradation and gold recovery. The obtained results provide a new insight about the photocatalytic recovery of gold from industrial wastewater and also shed light on the application of gold-decorated CN/WO3 − x as a catalyst for other photocatalytic applications.